2017
DOI: 10.1002/ijc.30634
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic variation within vitamin D receptor‐DNA binding sites and risk of basal cell carcinoma

Abstract: An increasing number of studies have reported a protective association between vitamin D and cancer risk. The vitamin D endocrine system regulates transcriptional programs involved in inflammation, cell growth and differentiation through the binding of vitamin D receptor (VDR) to specific VDR elements. However, limited attention has been given to the role of variation within VDR binding sites in the development of basal cell carcinoma (BCC). Across 2,776 previously identified VDR binding sites, we identified 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Another study identified two new SNPs in VDR binding sites (rs16917546 and rs79824801) associated with BCC risk. This study also confirmed the association of the rs3769823 SNP in the VDR binding site with increased BCC risk [117], while a study performed on a population in the mid-south of the USA (96 cases vs. 100 controls) showed that subjects with BsmI SNP had two times higher probability of developing NMSC in comparison to controls [38]. Thus, VDR polymorphisms should be considered as factors related to NMCS risk; however, additional studies are needed with larger population cohorts.…”
Section: Vitamin D Receptor (Vdr)supporting
confidence: 77%
See 1 more Smart Citation
“…Another study identified two new SNPs in VDR binding sites (rs16917546 and rs79824801) associated with BCC risk. This study also confirmed the association of the rs3769823 SNP in the VDR binding site with increased BCC risk [117], while a study performed on a population in the mid-south of the USA (96 cases vs. 100 controls) showed that subjects with BsmI SNP had two times higher probability of developing NMSC in comparison to controls [38]. Thus, VDR polymorphisms should be considered as factors related to NMCS risk; however, additional studies are needed with larger population cohorts.…”
Section: Vitamin D Receptor (Vdr)supporting
confidence: 77%
“…Moreover, VDR activity can be influenced by single-nucleotide polymorphisms (SNPs) [254]. This plays, for example, a role in the etiology of nonmelanoma skin cancers (NMSC) and melanoma [38,54,104,111,117]. Interestingly, CYP11A1-derived D3 hydroxyderivatives without a hydroxyl group at C1α display a subset of the activities possessed by 1,25(OH) 2 D3 (see above) and lack calcemic activity, acting as biased agonists on the VDR [197,207].…”
Section: Vitamin D Receptor (Vdr)mentioning
confidence: 99%
“…In a huge study reported by Lin et al , involving over 17,000 BCC cases compared to over 250,000 controls, 2 single-nucleotide polymorphisms (SNPs) at new loci were found related to BCC risk. The study pointed out that inherited common variations in VDR are linked to BCC development (77). Another study performed by Kaukinen et al , also in 2017, using an animal skin model, showed that MCs expressing VDR are involved in UV-mediated immunosuppression.…”
Section: Non-melanoma Tumors: Squamous Cell and Basal Cell Skin Carcimentioning
confidence: 99%
“…Of particular interest, our integrative approach revealed a strong enrichment of BCC susceptibility genes (24% of SMR and 38% of SMR-HEIDI candidate genes) involved in regulatory T cell (T Reg ) activity. These include previously identified GWAS loci including CTLA4 [10], IRF4 [12], VDR [8], and SMC2 [10]. T Regs are essential for maintaining immune homeostasis by limiting effector T cell activity against foreign antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have played a key role in identifying the polygenic effects that confer susceptibility to BCC. Loci have been attributed to a wide variety of biological processes including photoprotection, cellular trafficking, cytoskeletal organisation, cell motility/migration, skin biology, ectoderm/ mesoderm differentiation, cell death, telomere biology, immune, tumour progression, DNA repair, and cell cycle regulation [6][7][8][9][10][11][12]. Although GWAS provide a framework for identifying putative susceptibility loci, they rarely identify causal genes, predominantly due to the complicated linkage disequilibrium (LD) structure of the genome, in addition to the fact that genetic variants can affect phenotype via distant regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%